2007
DOI: 10.1111/j.1469-7580.2007.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of muscular dystrophy on the craniofacial shape of Mus musculus

Abstract: Skeletal anomalies are common in patients with muscular dystrophy, despite an absence of mutations to genes that specifically direct skeletogenesis. In order to understand these anomalies further, we examined two strains of muscular dystrophy (laminin-and merosin-deficient) relative to controls, to determine how the weakened muscle forces affected skull shape in a mouse model. Shape was characterized with geometric morphometric techniques, improving upon the limited analytical power of the standard linear meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…At the level of individuals, mechanical stress arising from muscle function during mastication might be partially or completely responsible for the growth of morphogenetic components that serve as points of muscle attachment (Mavropoulos et al 2004; Jones et al 2007; Rot‐Nikcevic et al 2007; Zelditch et al 2009). In conjunction with the muscle attachment sites, the points where reaction forces are observed (jaw joints and bite points) are also strained during mastication (Herring et al 2001; Ross and Metzger 2004).…”
Section: Discussionmentioning
confidence: 99%
“…At the level of individuals, mechanical stress arising from muscle function during mastication might be partially or completely responsible for the growth of morphogenetic components that serve as points of muscle attachment (Mavropoulos et al 2004; Jones et al 2007; Rot‐Nikcevic et al 2007; Zelditch et al 2009). In conjunction with the muscle attachment sites, the points where reaction forces are observed (jaw joints and bite points) are also strained during mastication (Herring et al 2001; Ross and Metzger 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cheverud (1982, 1995) suggested that environmental integration is strong in functionally or developmentally integrated traits when the neurocranium and viscerocranium are treated as two different units, whereas genetic integration is stronger than environmental and phenotypic integration when the skull is considered as a whole. This differential growth rate probably reflects the functional demands of the viscerocranium and the application of muscular forces to the facial skull on aging (Lightfoot & German, 1998; Jones et al ., 2007). Evidence from the present study supports the idea that the functional demands of the viscerocranium are greater after birth and that, to reach functional adult proportions, growth in this area occurs at a higher rate.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of the masticatory muscles will be reported, comparisons with previous work will be made, and current controversies will be addressed. Given the importance of rodents and knowledge of their musculature to many scientific disciplines other than anatomy, in particular evolutionary developmental biology (Hallgrímsson et al, 2007; Jones et al, 2007; Hallgrímsson and Lieberman, 2008; Parsons et al, 2008), it is felt that such a review is timely and necessary.…”
mentioning
confidence: 99%